Enhancement of Raman scattering from molecules placed near metal nanoparticles - Barbiellini, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
Large Raman scattering cross sections from molecules on surfaces of metallic nanoparticles are described within a renormalization-group theory. In this approach the valence electrons of the molecules are embedded in an effective medium described by a dielectric function, which integrates out the effect of the plasmonic excitations of the metallic nanoparticles. The source of the enhanced photon inelastic scattering is produced by the resonant excitation of surface plasmons at the metallic nanoparticles. A similar theory has been successfully used to explain the resonant x-ray inelastic scattering and the behavior of nonlinear susceptibilities at the x-ray edges.